Brain correlates of stress-induced analgesia - Kirsch, Pinar; Diers, Martin; Diener, Slawomira; Rance, Mariela; Wessa, Michèle; Flor, Herta (Pain, 2010)
Stress-induced analgesia (SIA) refers to a reduced pain response after stress exposure, which is mediated by descending pain-inhibitory circuits and may be an indicator of adequate centrally mediated pain control. We used functional magnetic resonance imaging to assess brain mechanisms of SIA in 21 healthy participants. Using a block design series of mildly painful pressure stimuli were applied to the left medial phalanx of the second digit during functional magnetic resonance imaging. Mental arithmetic combined with increasing levels of noise was used as a stressor. Verbal ratings, changes in blood pressure and heart rate confirmed the validity of the stress induction. Post-stress pain thresholds and pain tolerance were significantly higher and post-stress pain and unpleasantness ratings were significantly lower compared to pre-stress levels. SIA led to an increase of the blood-level-dependent oxygenation response in the primary somatosensory cortex, bilaterally in the anterior insula, and secondary somatosensory cortex. The increase in pain tolerance correlated significantly with activation in the rostral anterior cingulate cortex and pain unpleasantness with activation in the dorsal anterior cingulate cortex. SIA seems to activate similar brain networks as placebo analgesia or analgesia mediated by diffuse noxious inhibitory controls and involved sensory, affective and cognitive modulatory circuits.
Gesehen am 03.07.2024